Evaluasi Pembelajaran IPA Model Discovery Learning Menggunakan Model Countenance Stake - Putri Rahadian Dyah Kusumawati (LITERASI (Jurnal Ilmu Pendidikan), 2020)
This research aims were: (1) the quality of preparation, (2) the quality of implementation, and (3) the learning outcomes of students in application of learning science in Curriculum 2013. This research was model evaluation research based on Countenance Stake model. The population in this study was teachers and students in seventh grade of Junior High School. This research was conducted in Junior High School that was applying Curriculum 2013 in Bantul region. The teacher sample was determined by purposive sampling technique. The student sample was determined by proportional random sampling technique. The data were collected using document preparation review sheets, classroom observations, student and teacher questionnaires, and document of student learning outcomes. The data were analyzed by descriptive quantitative technique. The results indicated a strong concerned between the quality of teacher preparation, implementation and student learning outcomes. The result of this research show that: (1) the quality of preparation of learning science in Curriculum 2013 was categorized good (t-score = 50,51), (2) the quality of implementation of learning science in Curriculum 2013 was categorized good (t-score = 51,32), (3) the result of student learning outcomes was categorized good (t-score = 50,59).